(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the importance of databases and electronic libraries in learning English. The research methodology includes literature review and statistical analysis. The findings demonstrate the effectiveness of resources and the opportunities they provide for learners.